Landscape experiences as paths to new perceptions and experiences - Risso, Luciene Cristina [UNESP] (Univ Federal Fluminense, 2020)
The present text will propose to interpret the environmental experiences carried out by UNESP university students of Geography course in the extractive reserve of Mandira, quilombola community of Cananeia (SP), verifying through narratives and field sketches there was interiorization of new perceptions and environmental experiences. It can be said that the experiences provided stimulated in most students a rediscovery of knowledge and values producing a new awareness directed to the conduct of involvement / belonging to environmental issues. It is attentive to the crucial role of the fieldwork in Geography as a possibility of immersion in the landscapes and contact with each other, inspiring new environmental consciousnesses, feelings and attitudes.
Keywords: Field sketches; Fieldwork; Narratives; Humanist Geography